Hydrochar production from watermelon peel by hydrothermal carbonization. (October 2017) - Chen, Xuejiao; Lin, Qimei; He, Ruidong; Zhao, Xiaorong; Li, Guitong
Highlights: HTC (260 °C, 1 h) converted about 54% of watermelon peel dry matter into hydrochar. BTX and VOCs in hydrochar may induce environmental risks after soil amendment. The spent liquor can be used as fertilizer for its abundant nutrient elements. Abstract: Watermelon peel waste was hydrothermally carbonized under 190 °C and 260 °C for 1 h, 6 h, and 12 h, respectively. The hydrochar and spent liquor were collected and assayed for their properties. The results indicated that hydrochar yield was 2–5% and 46–95% on fresh and dry matter, respectively. Low temperature (190 °C) was conducive to high conversion efficiency. The hydrochar had higher C/N ratio (22.19–26.86), more alkyl C, aryl C, and carbonyl C, but lower H/C (0.98–1.22) and O/C ratios (0.13–0.38), and less O-alky C, carboxylic C, compared with feedstock. So the aliphaticity decreased, whereas aromaticity increased significantly, especially under severe conditions. It should be watchful for that the toxic compounds in hydrochar may induce environmental risk while it is amended into soil. The spent liquor with abundant nutrients could be used as a fertilizer. Further work is required for testing the application in soil.